2014
DOI: 10.1002/adfm.201402532
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Monte Carlo Study of the Sensitivity of OLED Efficiency and Lifetime to Materials Parameters

Abstract: wileyonlinelibrary.comand excitonic processes and determining the values of the relevant material-specifi c parameters, ii) supporting the layer stack design process by providing an effi cient route for developing understanding of the benefi ts and disadvantages of the use of novel materials and layer stack concepts. The third (vertical) axis in the fi gure indicates examples of the performance characteristics which may be studied using the simulations. We envisage that simulations can be used to clarify the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 46 publications
(91 reference statements)
2
79
1
Order By: Relevance
“…The excitons are allowed to decay with default radiative and nonradiative lifetimes τ rad,0 = 1.84 μs and τ nr,0 = 5.52 μs, respectively, so that the effective lifetime is τ 0 = 1.38 μs. These are realistic values for the phosphorescent orange-red emitter bis(2-methyldibenzo[f,h]quinoxaline)(acetylacetonate)-iridium(III) [Ir(MDQ) 2 (acac)] [20]. However, the effect of varying τ while keeping the ratio τ nr /τ rad fixed was also studied.…”
Section: A Methodsmentioning
confidence: 99%
“…The excitons are allowed to decay with default radiative and nonradiative lifetimes τ rad,0 = 1.84 μs and τ nr,0 = 5.52 μs, respectively, so that the effective lifetime is τ 0 = 1.38 μs. These are realistic values for the phosphorescent orange-red emitter bis(2-methyldibenzo[f,h]quinoxaline)(acetylacetonate)-iridium(III) [Ir(MDQ) 2 (acac)] [20]. However, the effect of varying τ while keeping the ratio τ nr /τ rad fixed was also studied.…”
Section: A Methodsmentioning
confidence: 99%
“…In contrast to the Förster rate, the Dexter type energy transfer rises due to the exchange interaction and may occur between next neighbors [92]. Following [22], the Dexter type hopping is modeled as a Miller-Abrahams hopping defined by:…”
Section: Excitonsmentioning
confidence: 99%
“…A separation rate a s exs = 1/τ s exs is enabled if the singlet is located at an interface. Dissociation of a triplet exciton is interpreted as an electron hopping from its current position towards an unoccupied neighboring site [21][22][23]. The separation rate a t exs is calculated with the Miller-Abrahams rate using an energy difference of ∆E = ∆E LUMO + E CT,B − E t B .…”
Section: Excitonsmentioning
confidence: 99%
See 1 more Smart Citation
“…They also show the more experimentally-accessible luminance vs. lifetime relationship, showing that lifetime reduces with increasing current (Figure 9a) and disorder ( Figure 9b). Coehoorn et al [442] have also used a KMC model to examine degradation in OLEDs, and found that exciton-polaron quenching was the major cause of both internal quantum efficiency (IQE) roll-off and degradation. This in turn allowed development of an analytical expression that relates the lifetime to parameters available in steady-state measurements.…”
Section: Organic Light-emitting Diodes (Oleds)mentioning
confidence: 99%